Analyzing The Pathology And Immune Response To New And Re-Emerging Infectious Agents (Journal of Pharmaceutical Negative Results, 2022)
Background: Infectious diseases especially the ones that are new and recurring constitute threats to the wellbeing of the global population. It is equally important to know this for the development of the intervention with full understanding of the illness and the immune system. Updated outbreaks of new pathogenic agents explain the necessity of further investigations for the basis of population and clinical approaches to these illnesses.Objectives : To compare immune reactions in the patients, infected with the new and re-emerging infectious agents and reveal the regularity that could influence the treatment. Study design: A Cross Sectional Study.Place and duration of study. Department of Pathology Watim medical and dental college, rawat from jan 2021 to July 2021Methods : The study involved a sample of 150 patients whom all developing emerging infectious diseases. Serum samples were taken for the purpose of measuring marker of immune responses. For histopathological evaluation, normal methods of staining were employed over the tissue specimens. Paired comparison of various immune responses were done using standard deviation, t-test with p-value to determine the significant difference between various patients’ group.Results : this Cross-sectional analysis of 150 patient revealed that there is altered immune defense system among the patients. The standard deviation in immune marker level was 12. 5 with a p<. 03 which truly highlights the fact that there is indeed a difference between severe and mild symptom patients. The pathological analysis showed that all the tissues which were affected had similar inflammation patterns and it was highly probable that inflammation had significant effect on the overall severity of the diseases.Conclusion : The study also draws particular attention toward the actual immune response as to its contribution toward severity of the infection. They may help in designing specific therapeutic strategies and enhancing the benefits received wherever genomics analysis and molecular modelling of host-pathogen interactions is required.